Speciesism and the perception of animals - doi: 10.4025/actascihumansoc.v33i1.7827 - Coltro, Fábio Luiz Zanardi (2011)
Are there limits to how human beings can legitimately treat non-human animals? Or may we treat them any way we please? If there are limits, what are they? Are they sufficiently strong, as some people suppose, not to lead us into speciesism and to reduce, if not eliminate altogether, our use of non-human animals in “scientific” experiments for our benefit? To completely evaluate this issue, I shall contrast it to two different questions: are there limits to how we can legitimately treat rocks? And: are there limits to how we can legitimately treat other human beings? These questions are linked to the concept of speciesism, a neologism created by Richard Ryder in 1970 to describe the relationship of prejudice by one species towards another. The most common form of speciesism is the animal kind, whereupon one species (Human beings) have a prejudiced relationship with another species (non-human beings). This work aims to explain how we, human beings, perceive other species and how we act with regard to others.